Fatal acute intoxication of accidentally ingested nifedipine in an infant – A case report. (January 2017) - Yamamoto, Hiroki; Takayasu, Tatsunori; Nosaka, Mizuho; Kimura, Akihiko; Ishida, Yuko; Kawaguchi, Takashi; Fukami, Mie; Okada, Misato; Kondo, Toshikazu
Highlights: We report a death caused by acute nifedipine intoxication in two years old infant. He orally ingested nifedipine which had been prescribed to his grandfather. It was considered that he ingested nifedipine in mistake for ramune confectionery. Blood concentration of nifedipine was higher than that of past infant fatal case. There was a few fatal report of accidental ingestion of nifedipine in infant. Abstract: A fatal case of acute nifedipine intoxication in a two-year-old boy is presented. The boy accidentally orally ingested an unknown amount of his grandfather's nifedipine (40 mg/tablet), mistaking it for a ramune confectionery. Despite intensive medical treatment, his death was confirmed at 31 h after the accidental ingestion. The forensic autopsy revealed that there were neither pathological alterations or injuries in all of the organs. Toxicologically, nifedipine could be detected at the concentrations of 0.463, 0.669 and 13.0 μg/g in cardiac blood, peripheral blood and stomach contents, respectively. These concentrations were evaluated as fatal levels, and the cause of death was diagnosed as acute nifedipine intoxication. Recently, the number of infants and children who accidentally ingest drugs in the home is increasing. This case report prompts forensic pathologists and toxicologists to emphasize that children are always exposed to the risk of accidental drug ingestion in daily life.